2020
DOI: 10.1021/acschemneuro.0c00154
|View full text |Cite
|
Sign up to set email alerts
|

Circular Dichroism Spectroscopy Identifies the β-Adrenoceptor Agonist Salbutamol As a Direct Inhibitor of Tau Filament Formation in Vitro

Abstract: Circular dichroism spectroscopy identifies the β-adrenoceptor agonist salbutamol as a direct inhibitor of tau filament formation in vitro.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 80 publications
0
14
0
Order By: Relevance
“…Salbutamol is a frequently used, relatively cheap, and well established selective β2AR agonist available on the Dutch market [ 25 ]. The in vitro study Townsend et al [ 5 ]. reported that salbutamol is able to decrease the rate and yield of filament formation and also that it could inhibit tau’s structural change into aggregates [ 5 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Salbutamol is a frequently used, relatively cheap, and well established selective β2AR agonist available on the Dutch market [ 25 ]. The in vitro study Townsend et al [ 5 ]. reported that salbutamol is able to decrease the rate and yield of filament formation and also that it could inhibit tau’s structural change into aggregates [ 5 ].…”
Section: Discussionmentioning
confidence: 99%
“…AD is a progressive and irreversible brain disorder with loss of behavioral abilities and cognitive functioning among which reasoning, remembering, perception, language comprehension, and thinking [ 4 ]. Pathological hallmarks of AD are the deposition of tau and amyloid-β (Aβ) in the brain which on the long run can cause neurodegeneration due to the formation of insoluble neurofibrillary tangles and amyloid fibrils (Aβ plaques) [ 5 ]. AD is also characterized by chronic inflammation [ 6, 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…We observed that the albuterol was associated with a consistent 22% reduced risk of AD (HR 0.78, 95% CI 0.74-0.83) in OneFlorida and a 22% reduced risk of AD (HR 0.78, 95% CI 0.76-0.80) in MarketScan. Previous literature generated AD signals from in-vivo screening 28 or rats models 29 (See Supplementary Table 9 for review details). To the best of our knowledge, our work showed the first RWD signal of albuterol for AD.…”
Section: Resultsmentioning
confidence: 99%
“…More recently, 1280 approved small molecule approved drugs were screened for TH PC potential and one of the hits was levalbuterol, the active molecule in salbutamol/albuterol [157]. This drug is a bronchodilator widely administered for chronic obstructive lung disease and asthma and has been linked to reduced risk and delayed progression of PD and other neuropsychiatric and neurodegenerative disorders [158][159][160][161][162]. Of interest, salbutamol is also suggested to improve the response to L-DOPA therapy in PD by enhancing L-DOPA transport across the BBB [163][164][165].…”
Section: Pharmacological Chaperonesmentioning
confidence: 99%